"[A] country where one cannot wish to be" : Place and the Mythic Imaginatio in Wong Phui Nam’s "How the Hilss are Distant" - Jeyam, Leonard (SARE: Southeast Asian Review of English, 2017)
In this article I shall delve into the heart of Wong’s early notions of a homeland which according to him is a "country where one cannot wish to be" and I shall also probe what he means by a local writer bringing "a naked and orphaned psyche" into his work. His use of modernist myt in all his early verse, especially in the sequence How the Hills are Distant, will demonstrate how an early Malaysian writer such as Wong could easily lead to his work having a moral and political non-viability in the postcolonial context.